Criminology on Trump - Barak, Gregg (Crinmes of the powerful, 2022)
Family dynamics, privileged disadvantages, and coming of age -- A lifetime of deviance, deception and dishonesty, 1970-2016 -- Weaponizing the law, litigation, and legality -- Campaigns and policies of adversity, harmfulness, and divisiveness -- A sinkhole of organizational corruption -- State organized abuses of power and obstruction of justice -- Pardons, prosecutions, and the politics of punishment -- Insurrection, divided selves, and the aftermath of a failed coup.